Semantic Foundations Of Punctuation In English: Based On The Materials Of Dramatic Works - Yuldosheva Mekhrigul Nabiyevna (Zien Journals, 2025)
This article explores the semantic underpinnings of punctuation in English, focusing on dramatic texts as a distinctive genre where punctuation not only serves syntactic clarity but also conveys tone, rhythm, emotion, and intention. By examining selected dramatic works — particularly plays by Shakespeare, Tennessee Williams, and Harold Pinter — this paper investigates how punctuation functions semantically to shape dialogue, influence interpretation, and construct meaning. The study argues that punctuation in dramatic discourse transcends grammatical structure and becomes a vital tool for character development and dramatic effect
Keywords: punctuation; pause; emphasis